Olga Tokarczuk w Rumunii - Geambașu, Constantin (Postscriptum Polonistyczne, 2020)
The author discusses the reception of Olga Tokarczuk’s works in Romania on the basis of translations, critical essays and radio and press interviews. Olga Tokarczuk is the best-known contemporary writer from Central Europe in Romania, thanks to numerous translations (almost all of her novels have been translated into Romanian, except The Books of Jacob, due to be published next year). An important role in the dissemination of her works has been played by the Polirom publishing house in Iași, which published a special series devoted to Tokarczuk. The quality of the translations of the Polish novelist’s texts is also high. Particular credit for this goes to Cristina Godun, a specialist in Polish Studies, who has managed to render the peculiarities of Tokarczuk’s narrative and style in Romanian. The paper also briefly discusses the difficulties encountered during the translation of Tokarczuk’s texts.